Tephrostratigraphy of Jurassic-Cretaceous boundary beds of Western Siberia - Panchenko Ivan Vladimirovich; Rogov Mikhail; Sobolev Ivan Dmitrievich; Latyshev Anton; Zakharov Victor (Russian Journal of Earth Sciences, 2022)
The age of tuffaceous interlayers, represented by tuffs and tuffites, which are common in the Upper Jurassic-Lower Cretaceous deposits of Western Siberia (the Bazhenovo, Tutleim and Frolov Formations), is discussed. The nature of these interlayers is associated with the subglobal (transfer of more than 1--2 thousand km) spread of volcanic ash (0.001--0.1 mm) and its sedimentation and burial in a vast epicontinental marine basin during episodes of low sedimentation rates, weak hydrodynamic activity and in the absence of bioturbation. Despite the extremely low thickness of these pyroclastic layers (<1 mm -- first cm), they are systematically noted in the drill core at certain stratigraphic levels. Tuffs and tuffites are clearly recognized due to sharp boundaries and contrasting color and mineral composition comparing to the host rocks. Moreover, these layers often demonstrate exceptionally bright luminescence in yellow and orange tones in the ultraviolet. Some of these pyroclastic layers can be traced over a vast area (more than 700,000 sq km) and hence can be used as isochronous stratigraphic markers. Considering the importance of the information about the distal pyroclastics in sedimentary strata, we have summarized data on boreholes in Western Siberia, containing tuffs and tuffites in the Upper Jurassic - Lower Cretaceous. Detailed linking of interlayers by drilling depth and geophysical logging was performed. The findings of more than 370 tuff and tuffite interlayers in the core of 136 wells have been catalogued. The age of tuffaceous interlayers is justified by the combination of lithostratigraphic and biostratigraphic methods, and geophysical logging. The key ammonite taxa recovered from tuff-bearing boreholes are figured. A brief description of the zones of the Ryazanian stage of Western Siberia and the principles of their identification are given. We suggest to replace the type index of the Surites analogus zone with S. subanalogus. The described sequence of tuffaceous interlayers is combined into 8 sub-regional pyroclastic levels traced throughout the central part of Western Siberia in the Middle Volgian (4 pyroclastic levels), Ryazanian (3 levels) and Lower Valanginian (1 level) intervals. The trace elements content composition of tuffaceous layers is characterized. The enrichment of rare earth elements in the direction from the oldest to the youngest interlayers ones was revealed, and the ratios Gd/Yb, Ho/Yb, Yb/Lu, Zr/Hf, Nd/Sm determine the stratigraphic correspondence of the tuffaceous interlayer to the subregional pyroclastic level. Our results can be used as a tephrostratigraphic scale for the Jurassic-Cretaceous boundary beds. Catalog of finds of Upper Jurassic -- Lower Cretaceous tuffs and tuffites in the core of wells in Western Siberia [https://doi.org/10.2205/2022ES000817-data] in text format is available on the website of the Earth Sciences Database Repository (BDNS) [http://esdb.wdcb.ru/], located at the Geophysical Center of the Russian Academy of Sciences.